Women, Digital Politics, and the Dynamics of Hateful Extremism: Reassessing Indonesia’s 2019 Election in the Contemporary Era - Solikhah Yuliatiningtyas (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2025)
This article reassesses the dynamics of women’s political participation, digital mobilization, and the rise of hateful extremism during Indonesia’s 2019 presidential election, demonstrating their continued relevance in the country’s current digital-political landscape. Using Critical Discourse Analysis supported by interviews with politicians, journalists, and activists, as well as field observations from 2014 to post-2019, the study reveals how e-political campaigns strategically instrumentalized religious narratives, familial values, and gendered emotional appeals to mobilize conservative women at unprecedented scale. Women’s participation in the 212 Movement and related “Aksi Bela Islam” actions illustrates how female supporters became central actors in amplifying identity-based grievances and online hate speech, contributing to heightened polarization and, ultimately, the May 2019 post-election riots. To contextualize these findings in the present era, the article incorporates updated insights from Indonesia’s 2024 electoral environment, marked by a significant rise in disinformation—over 1,292 reported cases—and the increasing use of Artificial Intelligence (AI) in political communication. While digital mobilization in 2019 relied heavily on viral messaging, moral panic, and influencer-driven polarization, the 2024 election cycle demonstrates a technological shift: AI-generated images, synthetic personas, and automated content now intensify narrative manipulation and accelerate the spread of hate speech. These developments show that the mechanisms enabling women’s mobilization and digital extremism during the 2019 election have not disappeared; they have instead evolved through more sophisticated technological tools. By integrating perspectives from gender studies, political communication, and digital media, this study argues that Indonesia’s democratic vulnerabilities are deeply shaped by the intersection of gendered mobilization, religious identity politics, and rapidly advancing information technologies. The article concludes that the lessons of 2019 should be understood not as historical artifacts but as foundational patterns that continue to influence Indonesia’s electoral dynamics and digital political behavior today.